Organic Chemistry I - Liu, Xin (Open textbook library., 2021)
An open textbook that is suitable for the first semester of Organic Chemistry. Basic concepts of the structures and reactivities of organic molecules are covered in this open textbook. Besides the fundamental discussions of organic acids-bases, stereochemistry, IR and NMR, this book also includes the topics of substitution and elimination reactions, radical substitution of alkanes, preparation and reactions of alkenes and alkynes.